2012
DOI: 10.1002/jso.23307
|View full text |Cite
|
Sign up to set email alerts
|

Intentions for bilateral mastectomy among newly diagnosed breast cancer patients

Abstract: Background Recent trends suggest that bilateral mastectomy (BM) is on the rise among women diagnosed with unilateral breast cancer. Few studies have investigated the factors associated with the decision to have more aggressive surgery among young, high risk patients. Methods As part of a larger study, 284 women aged 50 and under completed an initial survey within six weeks of a breast cancer diagnosis. We assessed sociodemographics, medical and family history variables, treatment recommendations, preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Levels of decisional uncertainty in this study as measured by the DCS (mean score (µ) = 15.5) were comparable to or lower than those found in other studies of women making healthcare decisions, such as mastectomy after a breast cancer diagnosis (DCS µ = 17.4) [30], prenatal testing after infertility (DCS µ =22.1) [31], or antidepressant use during pregnancy (DCS µ = 26.2) [32]. They are also lower than levels observed in studies of men and women making decisions about reconstructive knee surgery (DCS µ = 37.4-42.7) [33] or men deciding on prostate cancer treatment options (DCS µ=35.7) [34].…”
Section: Discussionsupporting
confidence: 72%
“…Levels of decisional uncertainty in this study as measured by the DCS (mean score (µ) = 15.5) were comparable to or lower than those found in other studies of women making healthcare decisions, such as mastectomy after a breast cancer diagnosis (DCS µ = 17.4) [30], prenatal testing after infertility (DCS µ =22.1) [31], or antidepressant use during pregnancy (DCS µ = 26.2) [32]. They are also lower than levels observed in studies of men and women making decisions about reconstructive knee surgery (DCS µ = 37.4-42.7) [33] or men deciding on prostate cancer treatment options (DCS µ=35.7) [34].…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that more women are choosing bilateral mastectomy for unilateral breast cancer (Yao, Stewart, Winchester, Winchester 2010). Preference for bilateral mastectomy in younger women has been associated with higher neuroticism, perceived risk for contralateral breast cancer and lower preference for lumpectomy with neuroticism viewed as an indicator of trait anxiety (King, O'Neill, Spellman, Peshkin, Valdimarsdottir, Willey et al 2013). Hence, it would seem vital to ensure effective communication about risk of recurrence and long term impact of surgical decisions in younger women undergoing neo-adjuvant chemotherapy as surgery approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors predicting choice of CPM included perception of risk [28,30], distress/anxiety [28,30], neuroticism [30], breast cancer knowledge [30], causal beliefs about cancer [31] and worry about BC recurrence [29]. However, only perception of risk was considered repeatedly across studies; the remaining factors were explored within single studies, thus the consistency of findings is unknown.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Psychological factors considered included perception of risk [28,30], distress/anxiety [28,30], neuroticism [30], breast cancer knowledge [30], causal beliefs about cancer [31] and worry about BC recurrence [29]. Three studies were cross-sectional [28,30,31]: one study [30] surveyed women within 6 weeks of a BC diagnosis whilst two of the studies [28,31] surveyed women after surgery. Only one study [29] employed a longitudinal approach.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%